The Inevitability of Sin - Timpe, Kevin (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2023)
Part of the traditional Christian doctrine of sin is the claim that, due to the effects of original sin, acts of sin are inevitable. Of course, our reflection on sinful actions is shaped by how we think about human freedom and divine providence more broadly. Some have argued that libertarians have a difficult time accounting for the inevitability of sin. This paper uses David Lewis’s work on counterfactuals and possible worlds to give an account of how the inevitability of sin can be understood. It then shows how both theological determinism and Molinism can give an account of sin’s inevitability so understood. In doing so, I show that sin’s inevitability only follows if we restrict our focus to certain possible worlds that share certain features with the actual world. But once such a restriction is made explicit, I then develop a framework for how the libertarian non-Molinist can also use a similar restriction to give an account of the inevitability of sin given original sin.